Nitrogen Split Application Can Improve the Stalk Lodging Resistance of Maize Planted at High Density - Qun Wang; Jun Xue; Guoqiang Zhang; Jianglu Chen; Ruizhi Xie; Bo Ming; Peng Hou; Keru Wang; Shaokun Li (Agriculture, 2020)
The decrease of maize stalk quality is an important reason for stalk lodging during the grain filling stage. In the present study, a maize cultivar was planted at densities of 7.5, 9.0, 10.5, 12.0, and 13.5 × 104 plants ha−1 and subjected to nitrogen application rates of 0, 270, 360, and 450 kg ha−1 (denoted as N0, N270, N360, and N450). The stalk breaking force, mechanical strength, carbohydrate content, and nitrogen content of basal internodes were determined to study the effects of nitrogen application rate on the stalk lodging resistance of maize under different planting densities with integrated watering and fertilization using drip irrigation. At densities of 7.5 to 10.5 × 104 plants ha−1, the stalk breaking force, rind penetration strength (RPS), and crushing strength (CS) of the basal internode decreased first and then increased with increasing nitrogen application rate, with the lowest values obtained for the N270 treatment. Meanwhile, at planting densities of 12.0 × 104 plants ha−1 and above, the stalk breaking force, RPS, and CS increased with increasing nitrogen application rate. The basal internode dry weight per unit length (DWUL) and total N content increased with increasing nitrogen application rate. The breaking force was significantly positively correlated with the DWUL and mechanical strength of the basal internode. The RPS showed a positive linear correlation with the contents of cellulose, lignin, and total N of the third internode. Under the split application of water and fertilizer, the maize stalk total dry matter and contents of cellulose, lignin, and total nitrogen increased with increasing nitrogen fertilization rate during the grain filling stage at high planting density, so the stalk lodging resistance improved.